Clinical considerations for optimal use of the polymyxins: A focus on agent selection and dosing. (April 2017) - Pogue, J.M.; Ortwine, J.K.; Kaye, K.S.
Abstract: Polymyxins have remained the drug of choice for treatment due to carbapenem-resistant Gram-negative bacilli. Unfortunately, the utility of these agents has been limited by a lack of pharmacokinetic understanding, a high toxicity rate, and an extremely narrow therapeutic index. Significant advancements have been achieved in the understanding of the polymyxins over the past decade, and have led to the recognition of several differences between available intravenous formulations. The purpose of this review is to discuss the implications of these differences, assess comparative efficacy and safety of the polymyxins, and provide recommendations for polymyxin dosing and selection.